Uji Antagonis Bakteri Rizosfer Potensial Proteolitik Terhadap Erwinia spp. dari Batang Tanaman Buah Naga (Hylocereus polyrhizus (Haw) Britt & Ros) - Mukarlina, Apriyani, Rahmawati, (Jurnal Protobiont, 2017)
Erwinia is one of the pathogenic bacterias that causes the rot disease in the stem of dragon fruit plant. The controlling of pathogen bacteria can be done by utilizing bacteria biological. The purpose of this study is to determine the potential proteolytic rhizosphere bacteria that is able in inhibiting bacterial members of the genus Erwinia spp. which is isolated from the stem of dragon fruit plant. The winter uses double test as the method to determine the ability of bacterial antagonist. Potential proteolytic rhizosphere bacteria are found in eight isolates belonging to the genus Erwinia (BN II and BN IV). The result of antagonistic test shows that TN I rhizosfere bacterial isolate of Erwinia BN II genus with inhibit zone diameter of 12,47 mm and BN IV isolate with a diameter of 11,91mm inhibition zone.